Preparation and Performance of Ni/Cr - C Coating on Stainless Steel Bipolar Plate of Fuel Cell - ZHANG Yan - na, WANG Li - da, SUN Wen, LI Rui, HE Yong - peng, SHU Xiang - quan, LIU Gui - chang (Cailiao Baohu, 2021)
For improving the corrosion resistance and surface conductibility of stainless steel bipolar plates, a Ni/Cr - C coating was prepared on the surface of 304 stainless steel by nickel preplating and trivalent chromium plating. The performance of coatings was characterized by FE - SEM, EDS, XPS, XRD and contact angle measurement. Results showed that at the deposition potential of -1.8 V(vs SCE), the Cr - C coating prepared from trivalent chromium plating bath was an amorphous coating without obvious micro - defects, and the water contact angle of the coating was 92.6°, indicating that the coating had a certain degree of hydrophobicity. The potentiodynamic test was performed at 70 ℃ in a simulated environment (0.5 mol/L H2SO4 + 2 mg/L HF), indicating that the corrosion current density of the stainless steel bipolar plate after the modification of the amorphous Cr - C coating was 0.8 μA/cm2, which was about 2 orders of magnitude lower than that of the original 304 stainless steel substrate. Meanwhile, the contact resistance of stainless steel bioplar plate was 4.5 mΩ·cm2 at a pressure of 140 N/cm2, and the conductivity was significantly improved.